Winning heads and hearts? How websites encourage prosocial behaviour. Issue 9 (4th July 2021) - Slattery, Peter; Vidgen, Richard; Finnegan, Patrick
ABSTRACT: This study examines how website specific factors promote prosocial behaviours in website visitors. After reviewing the literature, we hypothesise a structural model involving seven perceptions (ease of use, trust, negative affect, positive affect, aesthetics, information quality, and argument strength) and an interaction between positive and negative affect. We test our model by recording participants' perceptions and prosocial behaviours after their use of a website promoting volunteering and philanthropy. Two websites ('Amnesty International', and 'Casa Guatemala') are used. We find that website based appeals to both the head (i.e. perceptions of argument strength) and the heart (i.e. perceptions of positive and negative affect) motivate online prosocial behaviour, (i) that appeals to the heart are more effective than appeals to the head, (ii) that positive and negative appeals to the heart have similar effectiveness, and; (iii) that mixed appeals to the heart (i.e. simultaneous perceptions of both positive and negative affect) are ineffective.